Validation of actuator disc circulation distribution for unsteady virtual blades model. Issue 6 (November 2021) - Kusyumov, A. N.; Kusyumov, S. A.; Mikhailov, S. A.; Barakos, G. N.
Highlights: Unsteady actuator disk is an approach for simulation of a helicopter rotor wake. Considered actuator model is based on prescribed disk circulation distribution. Two kinds of trimming coefficients for the circulation distribution are considered. Actuator disk load is well agreed with a vortex theory and CFD simulation results. Abstract: The actuator disc method is an engineering approach to reduce computer resources in computational fluid dynamics (CFD) simulations of helicopter rotors or aeroplane propellers. Implementation of an actuator disc based on rotor circulation distribution allows for approximations to be made while reproducing the blade tip vortices. Radial circulation distributions can be formulated according to the nonuniform Heyson-Katzoff "typical load" in hover. In forward flight, the nonuniform disk models include "azimuthal" sin and cos terms to reproduce the blade cyclic motion. The azimuthal circulation distribution for a forward flight mode corresponds to trimmed conditions for the disk rolling and pitching moments. The amplitude of the cos harmonic is analysed and compared here with presented in references data and CFD simulations results.